2005
DOI: 10.1103/physrevb.72.155326
|View full text |Cite
|
Sign up to set email alerts
|

Photon-assisted electron-hole shot noise in multiterminal conductors

Abstract: Motivated by a recent experiment by L.-H. Reydellet et al., Phys. Rev. Lett. 90, 176803 (2003), we discuss an interpretation of photon-assisted shot noise in mesoscopic multiprobe conductors in terms of electron-hole pair excitations. AC-voltages are applied to the contacts of the sample. Of interest are correlations resulting from the fact that electrons and holes are generated in pairs. We show that with two out-of-phase ac-potentials of equal magnitude and frequency, applied to different contacts, it is pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 45 publications
(86 reference statements)
4
78
0
Order By: Relevance
“…An electronic HOM experiment has been proposed by Giovannetti et al [63]. HOM shot noise correlation of electron-hole pairs using two phase shifted ac voltages of weak amplitude (eV ac < hν) has been theoretically considered by Rychkov et al [43]. Up to now, the theoretical works have only addressed the case not discussed here of two single charges emitted from two ac driven quantum dot capacitors.…”
Section: Energy Domain: Spectroscopy Of the E-h Pairs Excitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…An electronic HOM experiment has been proposed by Giovannetti et al [63]. HOM shot noise correlation of electron-hole pairs using two phase shifted ac voltages of weak amplitude (eV ac < hν) has been theoretically considered by Rychkov et al [43]. Up to now, the theoretical works have only addressed the case not discussed here of two single charges emitted from two ac driven quantum dot capacitors.…”
Section: Energy Domain: Spectroscopy Of the E-h Pairs Excitationsmentioning
confidence: 99%
“…In this work, the theory of quantum partition noise of photon-created electron-hole pairs, equations (6-9), was experimentally checked from weak to large ac excitation and by varying the transmission. Motivated by this experiment, Rychkov et al [43] have theoretically shown that the electron and hole excitations contributing to noise in Eq. (9) are not statistically independent.…”
Section: Photo-assisted Shot Noisementioning
confidence: 99%
See 1 more Smart Citation
“…[18]. In both cases there is a correlation contribution to the noise [19]. The noise properties are completely different in the strong amplitude regime, V α,1 > ∼ ∆ α , when the SES can emit an electron or absorb an electron (i.e., emit a hole).…”
mentioning
confidence: 99%
“…However the approach is only applicable to two-dimensional devices, it is formulated in the framework of semi-empirical tight-binding, and does not include a self-consistent treatment of finite applied potential. Finally, a mesoscopic treatment for phononassisted current through multiterminal conductors was formulated by Rychkov et al 6 . While these multiterminal approaches address important issues, they neither treat the system in an ab initio fashion, including atomistic details, nor do they account for the self-consistent (SC) rearrangement of electrons as the bias and the current increase.…”
Section: Introductionmentioning
confidence: 99%